Late Post-Polio Functional Deterioration. Issue 2 (1st April 2003) - Howard, Robin
Abstract : ACUTE ILLNESS AND REHABILITATION In the first half of the 20th century, polio was one of the most feared of conditions in the UK and USA. Few people were unaffected during the epidemics of the 1940s and 50s, which preceded the introduction of immunization with the Salk inactivated vaccine in 1956 and the Sabin live attenuated vaccine in 1962. Patients remember the anxiety and mass hysteria surrounding each new outbreak of poliomyelitis, and fear of polio was often greatest amongst medical personnel, many of whom were affected (Gould 1995; Mulder 1991; Halstead 1995). This fear is graphically illustrated on the cover of Tony Gould's classic description of the history of poliomyelitis in the 20th century (Fig. 1) (Gould 1995). There are striking accounts of the acute illness – patients recall bathing in affected areas and developing non-specific fl u-like symptoms, often following periods of prolonged exertion (Russell 1949). When the diagnosis